Potential immunomodulatory effects of latent toxoplasmosis in humans - Flegr, Jaroslav; Stříž, Ilja (BMC infectious diseases, 2011)
BACKGROUND: About 30% of the population worldwide are infected with the protozoan parasite Toxoplasma gondii. Latent toxoplasmosis has many specific behavioral and physiological effects on the human organism. Modified reactivity of the immune system has been suggested to play a key role in many of these effects. For example, the immunosuppression hypothesis explains the higher probability of the birth of male offspring observed in Toxoplasma-positive humans and mice by the protection of the (more immunogenic) male embryos against abortion. METHODS: Here we searched for indices of immunosuppression in Toxoplasma-positive subjects by comparing clinical records of immunology outpatients. RESULTS: Our cohort study showed that the male patients with latent toxoplasmosis had decreased and the Toxoplasma-positive women had increased leukocyte, NK-cell and monocyte counts in comparison with controls. The B-cell counts were reduced in both Toxoplasma-positive men and women. The difference between Toxoplasma-positive and Toxoplasma-negative subjects diminished with the decline of the specific Toxoplasma antibody titre (a proxy for the length of infection), which is consistent with the observed decreasing strength of the effect of latent toxoplasmosis on human reproduction. The prevalence of toxoplasmosis in 128 male patients was unusually low (10.9%) which contrasted with normal prevalence in 312 female patients (23.7%) and in general population Prague (20-30%). CONCLUSIONS: Latent toxoplasmosis has immunomodulatory effects in human and probably protects men against some classes of immunopathological diseases. The main limitation of the present study was the absence of the data on the immunoreactivity of immune cells subpopulations. Therefore further studies are needed to search for indices of immunosuppression in human using more specific markers.
Keywords: lidé; Middle Aged; Adult; prospektivní studie; Female; imunologická tolerance; myši; Humans; Mice; Prospective Studies; Česká republika; Immune Tolerance; lidé středního věku; kohortové studie; Cohort Studies; mužské pohlaví; Toxoplasma; zvířata; Czech Republic; ženské pohlaví; toxoplazmóza; Animals; Male; Toxoplasmosis; asymptomatické nemoci; dospělí; Asymptomatic Diseases